The Effects of IHSG, Trading Volume, and Foreign Transactions on the Volatility of Blue-Chip Stocks in the Mining Sector - Rachma Agustina; M. Sadikin; M. Hendra Ferdinata (Proceeding International Conference on Accounting and Finance, 2025)
This study examines the influence of the Composite Stock Price Index (IHSG), trading volume, and net foreign buy/sell transactions on the volatility of three blue-chip mining stocks (ADRO, ANTM, and HRUM) on the Indonesia Stock Exchange in 2022. Employing quantitative methods via SPSS, this research seeks to clarify the varying impacts of these factors on stock price volatility. The findings reveal that IHSG, as a general market index, does not significantly affect the volatility of these specific stocks, highlighting that broader market indicators may be less relevant to individual stock behavior within the mining sector. In contrast, trading volume exerts a significant impact on the price movements of ADRO and ANTM, but not on HRUM, suggesting that investor trading activity strongly influences price volatility in certain blue-chip stocks. Additionally, net foreign buy/sell transactions show no significant effect on the volatility of any of the stocks studied, indicating that domestic investor behavior may play a more decisive role in these stock movements than foreign investments. These insights are valuable for investors focusing on blue-chip mining stocks, as they suggest that trading volume, rather than general index trends or foreign investment flows, could serve as a reliable predictor of price movements. Future research is recommended to incorporate other variables, such as local ownership and bid-ask spread, to further enhance understanding of stock price dynamics in Indonesia’s mining sector.